2018
DOI: 10.1021/jacs.8b04729
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Insights into the Eutectic Tripalmitin/Tristearin Binary System

Abstract: A molecular interpretation of the eutectic behavior of a binary mixture of tristearin (SSS) and tripalmitin (PPP) triglycerides was formulated using computer simulations and experimental techniques (calorimetry and X-ray scattering). A eutectic composition was identified using both experimental and computer simulation techniques at a composition of 70% PPP and 30% SSS, in agreement with previous findings in the literature. The decrease in the melting temperature at the eutectic composition can be ascribed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 51 publications
2
21
1
Order By: Relevance
“…1D). The relationship between small domain sizes and lower melting points has widely been reported for both eutectic 25,26 and monotectic systems 27 . Furthermore, our XRD analysis on structurally related odd-numbered carbon lipids (i.e., 1-heptadecanol, heptadecanoic acid and 16-heptadecynoic acid) showed larger lamellae (SAXS diffraction peaks), greater domain sizes, and different lateral packing of hydrocarbon chains (WAXS diffraction peaks) compared to avocado polyols ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…1D). The relationship between small domain sizes and lower melting points has widely been reported for both eutectic 25,26 and monotectic systems 27 . Furthermore, our XRD analysis on structurally related odd-numbered carbon lipids (i.e., 1-heptadecanol, heptadecanoic acid and 16-heptadecynoic acid) showed larger lamellae (SAXS diffraction peaks), greater domain sizes, and different lateral packing of hydrocarbon chains (WAXS diffraction peaks) compared to avocado polyols ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 86%
“…In contrast, avocadene and avocadyne are two structurally similar natural compounds that form a eutectic mixture at a molar ratio of 1:1 which translates to their efficient incorporation into a microemulsion-based delivery system. Mechanisms of eutectic formation are generally attributed to differences in i) molecular size and geometry, ii) polymorphic state, and iii) external fields (cooling and shear rates), which collectively leads to the formation of a more disordered crystal packing 25 . The XRD data presented here confirmed that molecular size and potentially polymorphic state contribute to the eutectic formation seen in AVO.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning SL type, emulsomes prepared using TS exhibited higher size compared to those prepared suing TP. TP and TS have very different melting points but very similar molecular structures (the fatty acid chains on tripalmitin (C16) differ from the fatty acid chains on tristearin (C18) by only two carbons) (Seetapan et al., 2010 ; Pizzirusso et al., 2018 ); the different size of these two triglycerides along with their different physicochemical properties could be responsible of the smaller vesicles TP-based compared to that with TS (Seetapan et al., 2010 ). Vyas et al.…”
Section: Resultsmentioning
confidence: 99%
“…A different case is the triclinic parallel subcell (β), in which the dense molecular packing prevents from the crystallization of non-isomorphic TAGs in the same crystal lattice. In this connection, a recent study, based on experimental data and computer simulations, associated the β immiscibility of PPP/SSS mixtures with the steric effect induced by the protrusion of large SSS end-chains into the interface between adjacent lamellas [ 85 ]. By taking this into account, it becomes evident the strict requirements of molecular resemblance and thermal behavior of solid solution-forming TAGs, which might be alleviated to some extent in the less stable crystalline packing.…”
Section: Phase Behavior In Mixtures Of Fully Saturated Tagsmentioning
confidence: 99%